Powdery mildew on spinach (Spinacia oleracea L.) - Nakova, Mariana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Symptoms resembling powdery mildew appeared on spinach crops during April and May in 2007. Infected plants have suppressed growth, smaller and degenerated young leaves. The affected leaves become yellowish and wilt in a short time. High temperatures and draught conditions cause drying out of the affected plants. The symptoms are similar to physiological degeneration but are found on single plants or on small groups of plants. When plants are carefully examined, fine, exogenic mycelium is found on the leave blades. The mycelium can be clearly seen close to the main veins where it becomes denser and forms mycelium patches. On the leaf and flower stalks and plant stems the mycelium is white and fine at the beginning, and later becomes grayish. Under microscope analysis ectophytic mycelia of exogenic origin and short chains of spores are observed. On short conidiophores, chains with two types of conidia are formed: macro conidia that are one-celled, colorless, thin-walled, elliptical to cylindrical, sized 24.5-28.4 x 17.5 μm; and micro conidia – ovoid to elliptical, sized 10.4-14.1 x 7.7 μm. Teleomorphs are found in groups or as a single structure mainly close to the leaf veins. They are roundish and have appendages with uncinate-circinate to helicoids apex, sized - 87.5-150 μm. Cleistothecia have 4-5 to 8 asci (68.0 x 38.0 μm), with 4 to 8 elliptical ascospores, sized 15.5-22.0 х 11.0-17.5 μm. The causal agent of powdery mildew on spinach found in Bulgaria has been identified as Uncinula spp. (Sawadaea spp.), Euoidium type anamorph, subspecies spinaciae.